The Emerging Role of Extracellular Vesicle-Associated RNAs in the Multiple Myeloma Microenvironment - Khalife, Jihane; Sanchez, James F.; Pichiorri, Flavia (Frontiers in Oncology, 2021)
Multiple myeloma (MM) is a cancer of terminally differentiated plasma cells (PCs) that develop at multiple sites within the bone marrow (BM). MM is treatable but rarely curable because of the frequent emergence of drug resistance and relapse. Increasing evidence indicates that the BM microenvironment plays a major role in supporting MM-PC survival and resistance to therapy. The BM microenvironment is a complex milieu containing hematopoietic cells, stromal cells, endothelial cells, immune cells, osteoclasts and osteoblasts, all contributing to the pathobiology of MM, including PC proliferation, escape from immune surveillance, angiogenesis and bone disease development. Small extracellular vesicles (EVs) are heterogenous lipid structures released by all cell types and mediate local and distal cellular communication. In MM, EVs are key mediators of the cross-talk between PCs and the surrounding microenvironment because of their ability to deliver bioactive cargo molecules such as lipids, mRNAs, non-coding regulatory RNA and proteins. Hence, MM-EVs highly contribute to establish a tumor-supportive BM niche that impacts MM pathogenesis and disease progression. In this review, we will first highlight the effects of RNA-containing, MM-derived EVs on the several cellular compartments within the BM microenvironment that play a role in the different aspects of MM pathology. We will also touch on the prospective use of MM-EV-associated non-coding RNAs as clinical biomarkers in the context of “liquid biopsy” in light of their importance as a promising tool in MM diagnosis, prognosis and prediction of drug resistance.